Feminine Archetypes and Their Roles in the Protagonist’s Spiritual Development in Raja Rao’s ‘The Serpent and the Rope’ - Sinha, Dr. Arpana (Journal of Advanced Research in English & Education; Vol 10 No 2 (2025): Journal of Advanced Research in English and Education, 2025)
Raja Rao’s magnum opus, ‘The Serpent and the Rope’ is a dense philosophical novel that chronicles the spiritual journey of its protagonist, Rama. This journey is intricately linked with his interactions with various female characters, who function as more than just romantic interests; they embody different facets of the feminine archetype, each contributing significantly to Rama’s spiritual and intellectual development. This article argues that the feminine presence in the novel is not merely a subplot but a central, transformative force. The women—Madeleine, Savithri, and to a lesser extent, the historical and mythological figures like Sita and Radha—serve as mirrors reflecting Rama’s inner state and as catalysts for his philosophical enquiries into the nature of reality, truth, and self. Madeleine represents the West’s rational, intellectual approach to spirituality, which ultimately proves insufficient for Rama’s deeply rooted Indian sensibility. Savithri, on the other hand, embodies the Eastern, intuitive, and non-dualistic understanding of reality, guiding Rama towards a realisation of Advaita Vedanta. Through these relationships, Rama grapples with the concepts of illusion (Maya) and ultimate reality (Brahman), using the feminine as a tangible symbol for his abstract philosophical dilemmas. The article explores how these archetypes are deeply rooted in Hindu mythology and philosophy, presenting a nuanced view of the feminine as both a source of worldly illusion and the ultimate path to spiritual liberation. The journey is not just a quest for love but a profound search for the self, in which the feminine becomes both the obstacle to be overcome and the divine grace that reveals the truth.